Entrepreneurial orientation and financial performance in the South African construction and materials sector: a focus on bricolage capability and absorptive capacity - Kanguwe, David Fikile (University of the Witwatersrand, Johannesburg Date of Issue *, 2024)
This thesis investigates the relationship between the entrepreneurial orientation (EO) and the sustainable financial performance of the South African construction and materials sector during the 2008-2019 period. In addition, it respectively investigates the moderating effects of environmental hostility on this relationship. Furthermore, in the context of environmental hostility, it investigates the respective moderating effects of the bricolage capability and the absorptive capacity on the same relationship. Moreover, it respectively investigates the moderating effects of organisational identity on the bricolage capability and absorptive capacity as well as the respective moderating effects of the bricolage capability- organisational identity and absorptive capacity-organisational identity interactions on this relationship. This research used a two-study approach to investigate this relationship and its moderating effects. The primary study collected survey data from 126 randomly selected firms in this sector. The secondary study collected secondary sustainable financial performance data from a purposively selected significant group of publicly listed firms. In both cases, data underwent analysis of variance and hierarchical regression. Post hoc analyses using the Tukey honest significance difference (HSD) test, slope analysis, and effect sizes were also used to complement these techniques. The results of the primary study indicate that the EO-sustainable financial performance relationship of this sector exhibited nonlinear, J-shaped behaviour. Furthermore, consistent with the EO-As-Experimentation perspective, the RBV and contingency theory, the results for the moderating effects do not support the hypotheses but rather indicate that all the moderating effects on this relationship were nonlinear suggesting that different configurations of these interactions, yielded different sustainable financial performance outcomes for different levels of EO. The results of the secondary study affirm those of the primary study. By using the theoretical framework of the resource-based and contingency theories, this thesis advances knowledge about the EO-firm performance relationship in the largely under- researched EO-As-Experimentation perspective by contributing a novel conceptual model. Through this conceptual model, this study contributes a unique managerial orientation to the persisting EO-ambidexterity debate in strategic entrepreneurship as well as to the South African construction and materials literature.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Management to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Entrepreneurial Orientation; Sustainable Financial Performance; Environmental Hostility; Bricolage Capability; Absorptive Capacity; Organisational Identity; SDG-8: Decent work and economic growth